Modelling of Network Mechanisms of Management in the Conditions of Organizational Development - Klochko, Elena N.; Fomenko, Natalya M.; Nekrasova, Victoria V. (International Review of Management and Marketing, 2016)
In this article, the organization is considered as open system, which due to virtualization of economy has an expansion of information and economic space. The information technologies applied in management of the enterprise allow to transform its organizational structure to a network form. Therefore, the organization gains new qualities not comparable to its previous traditional form of existence: management of the organization improve, there is a flexible reconfiguration of all resources of the company, its flexibility and adaptability to external and internal problems increases, competitiveness increases. The set of components of the virtual organization and features of its management has been analysed. Authors have developed the priorities valuation technique for the management decision on choosing the business model for the organization on the networking electronic market. Keywords: competitiveness, meta-market, business model JEL Classifications: M21; O10